The Effects of Omega-3 Supplementation Combined with Strength Training on Neuro-Biomarkers, Inflammatory and Antioxidant Responses, and the Lipid Profile in Physically Healthy Adults - Okut, Sedat; Ozan, Murat; Buzdagli, Yusuf; Ucar, Halil; Inac, Muhammet Rasit; Han, Muhammet Talha; Bayram, Esra (Mdpi, 2025)
Objectives: This study aimed to comprehensively investigate the physiological effects of omega-3 fatty acid supplementation combined with resistance training on the lipid profile, inflammatory and antioxidant responses, neuro-biomarkers, and physical performance parameters in physically healthy young adults. Methods: Thirty physically active male participants were randomly assigned to an experimental group (omega-3 + resistance training) or a control group (resistance training only). Over eight weeks, both groups performed a standardized resistance training program three times per week. The experimental group additionally received 3150 mg/day of omega-3 fatty acids (EPA and DHA). Pre- and post-intervention assessments included blood biomarkers (LDL, HDL, triglycerides, IL-6, TNF-alpha, CRP, GSH, MDA, BDNF, serotonin, and dopamine) and physical performance tests (1RM, CMJ, RSI, 10 m sprint, and Illinois agility). Results: The experimental group showed significant improvements in the lipid profile, with decreases in LDL and triglyceride levels and an increase in HDL levels. Levels of the inflammatory cytokines IL-6 and TNF-alpha were significantly reduced, while GSH levels increased and MDA levels decreased, indicating an enhanced antioxidant status. The neuro-biomarker analysis revealed increased levels of BDNF, dopamine, and serotonin. Physical performance tests demonstrated greater improvements in muscular strength, power, speed, agility, and reaction-based performance in the omega-3 group compared to controls. Conclusions: These findings suggest that omega-3 supplementation, when combined with resistance training, has a multi-systemic enhancing effect on both physiological markers and physical performance. This combination may represent a promising strategy for optimizing athletic adaptations and recovery in physically active populations. Future studies should further explore these effects across different populations and training modalities.
Keywords: Omega-3 fatty acids; resistance training; neuro-biomarkers; inflammatory response; antioxidant capacity